Epidemiology of musculoskeletal injury in military recruits: a systematic review and meta-analysis - Myles C. Murphy; Joanne Stannard; Vanessa R. Sutton; Patrick J. Owen; Brendon Park; Paola T. Chivers; Nicolas H. Hart (BMC, 2023)
Abstract Background Injuries are a common occurrence in military recruit training, however due to differences in the capture of training exposure, injury incidence rates are rarely reported. Our aim was to determine the musculoskeletal injury epidemiology of military recruits, including a standardised injury incidence rate. Methods Epidemiological systematic review following the PRISMA 2020 guidelines. Five online databases were searched from database inception to 5th May 2021. Prospective and retrospective studies that reported data on musculoskeletal injuries sustained by military recruits after the year 2000 were included. We reported on the frequency, prevalence and injury incidence rate. Incidence rate per 1000 training days (Exact 95% CI) was calculated using meta-analysis to allow comparisons between studies. Observed heterogeneity (e.g., training duration) precluded pooling of results across countries. The Joanna Briggs Institute Quality Assessment Checklist for Prevalence Studies assessed study quality. Results This review identified 41 studies comprising 451,782 recruits. Most studies (n = 26; 63%) reported the number of injured recruits, and the majority of studies (n = 27; 66%) reported the number of injuries to recruits. The prevalence of recruits with medical attention injuries or time-loss injuries was 22.8% and 31.4%, respectively. Meta-analysis revealed the injury incidence rate for recruits with a medical attention injury may be as high as 19.52 injuries per 1000 training days; and time-loss injury may be as high as 3.97 injuries per 1000 training days. Longer recruit training programs were associated with a reduced injury incidence rate (p = 0.003). The overall certainty of the evidence was low per a modified GRADE approach. Conclusion This systematic review with meta-analysis highlights a high musculoskeletal injury prevalence and injury incidence rate within military recruits undergoing basic training with minimal improvement observed over the past 20 years. Longer training program, which may decrease the degree of overload experienced by recruit, may reduce injury incidence rates. Unfortunately, reporting standards and reporting consistency remain a barrier to generalisability. Trial registration PROSPERO (Registration number: CRD42021251080).